Silver nanoparticle interactions with glycated and non-glycated human serum albumin mediate toxicity - Park, Hee-Yon; Chung, Christopher; Eiken, Madeline K.; Baumgartner, Karl V.; Fahy, Kira M.; Leung, Kaitlyn Q.; Bouzos, Evangelia; Asuri, Prashanth; Wheeler, Korin E.; Riley, Kathryn R. (Frontiers in Toxicology, 2023)
Introduction: Biomolecules bind to and transform nanoparticles, mediating their fate in biological systems. Despite over a decade of research into the protein corona, the role of protein modifications in mediating their interaction with nanomaterials remains poorly understood. In this study, we evaluated how glycation of the most abundant blood protein, human serum albumin (HSA), influences the formation of the protein corona on 40 nm silver nanoparticles (AgNPs) and the toxicity of AgNPs to the HepG2 human liver cell line. Methods: The effects of glycation on AgNP-HSA interactions were quantified using circular dichroism spectroscopy to monitor protein structural changes, dynamic light scattering to assess AgNP colloidal stability, zeta potential measurements to measure AgNP surface charge, and UV-vis spectroscopy and capillary electrophoresis (CE) to evaluate protein binding affinity and kinetics. The effect of the protein corona and HSA glycation on the toxicity of AgNPs to HepG2 cells was measured using the WST cell viability assay and AgNP dissolution was measured using linear sweep stripping voltammetry. Results and Discussion: Results from UV-vis and CE analyses suggest that glycation of HSA had little impact on the formation of the AgNP protein corona with protein-AgNP association constants of ≈2x107 M-1 for both HSA and glycated HSA (gHSA). The formation of the protein corona itself (regardless of whether it was formed from HSA or glycated HSA) caused an approximate 2-fold decrease in cell viability compared to the no protein AgNP control. While the toxicity of AgNPs to cells is often attributed to dissolved Ag(I), dissolution studies showed that the protein coated AgNPs underwent less dissolution than the no protein control, suggesting that the protein corona facilitated a nanoparticle-specific mechanism of toxicity. Overall, this study highlights the importance of protein coronas in mediating AgNP interactions with HepG2 cells and the need for future work to discern how protein coronas and protein modifications (like glycation) may alter AgNP reactivity to cellular organisms.